Servicio de producción de semillas. 1. Reunión Anual del Servicio de Producción de Semillas. Barranquilla (Colombia), 21-23 Sep 1970. - Instituto Colombiano Agropecuario, Bogotá (Colombia) (Instituto Colombiano Agropecuario, 2018)
Algodón-Gossypium herbaceum